Does Kisspeptin Belong to the Proposed RF-Amide Peptide Family? - Yun, Seongsik; Kim, Dong-Kyu; Furlong, Michael; Hwang, Jong-Ik; Vaudry, Hubert; Seong, Jae Young (Frontiers in Endocrinology, 2014)
Kisspeptin (KISS) plays a key role in regulating reproduction by binding to its receptor, GPR54 (KISSR). Because of the Arg-Phe (RF) sequence at its carboxyl terminus, KISS has been proposed to be a member of the RF-amide peptide family consisting of neuropeptide FF (NPFF), neuropeptide VF (NPVF), pyroglutamylated RF-amide peptide (QRFP), and prolactin-releasing hormone (PRLH). Evolutionary relationships of protein families can be determined through phylogenetic analysis. However, phylogenetic analysis among related peptide families, often fails to provide sufficient information because only short mature peptide sequences from full preprohormone sequences are conserved. Considering the concept of the coevolution of peptide ligands and their cognate receptors, evolutionary relationships among related receptor families provide clues to explore relationships between their peptides. Although receptors for NPFF, NPVF, and QRFP are phylogenetically clustered together, receptors for PRLH and KISS are on different branches of the phylogenetic tree. In particular, KISS has been proposed to be a member of the KISS/galanin/spexin family based on synteny analysis and the phylogenetic relationship between their receptors. This article discusses the evolutionary history of the receptors for the proposed RF-amide peptide family and proposes that, from an evolutionary aspect, KISS has emerged from an ancestor which is distinct from those of the other RF-amide peptides, and so should be classed separately.